1997
DOI: 10.1002/mds.870120327
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain tremor and hypertrophic olivary degeneration after pontine hemorrhage

Abstract: A severe rest tremor arose in a patient's right arm 9 months after a pontine tegmental hemorrhage. Magnetic resonance studies at 4 and 10 months showed residual hemosiderin in the pons and increasing hypertrophic olivary degeneration (HOD) affecting primarily the left olive. The tremor was refractory to pharmacotherapy (clonazepam, propranolol, and levodopa), but was reduced after implantation of a thalamic stimulator device. Although pontine hemorrhage is among several common causes of HOD, it has not previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 32 publications
1
37
1
Order By: Relevance
“…The peculiar mixture of rest, postural and kinetic tremor follows logically from this combination of pathology. Although attention has focused on the dentatorubral and dentatothalamic tract that forms the ascending limb of the dentate projection, components of the descending limb have also been implicated 6 . In particular, clinical evidence of a role for the rubroolivary tract is supported by experimental evidence of a rubroolivocerebellorubral loop 6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The peculiar mixture of rest, postural and kinetic tremor follows logically from this combination of pathology. Although attention has focused on the dentatorubral and dentatothalamic tract that forms the ascending limb of the dentate projection, components of the descending limb have also been implicated 6 . In particular, clinical evidence of a role for the rubroolivary tract is supported by experimental evidence of a rubroolivocerebellorubral loop 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal hypertrophy begins at 3 weeks, neuronal and glial hypertrophy peak at 8-9 months, pseudohypertrophy (neuronal dissolution and gemistocytic astrocytes) occurs thereafter, gradually leading to olivary atrophic degeneration 13,14 . MRI permits antemortem visualization of HOD, which appears as a characteristic signal-enhancing lesion in proton-density and T2-weighted images 6,8,15 . Although virtually all patients who develop palatal myoclonus after a brain insult will have HOD, not all patients with HOD develop palatal myoclonus 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In selected cases DBS and thermocoagulation may offer an alternative therapeutic strategy. 1,8,15,16,21,23,27 Kim, et al, 15 reported on a 26-year-old man in whom unilateral Vim thalamotomy almost completely abolished Holmes tremor that had been caused by a midbrain tumor. Two additional case reports of patients with a midbrain cavernous angioma 16,23 document good to excellent clinical improvements in Holmes tremor following thalamic Vim stimulation.…”
Section: Discussionmentioning
confidence: 99%